Introducing an ethical lobbying regulation in Indonesia: A policy recommendation - Dani Mochtar Isnaini; Yuda Alfarisi Nasution (Komisi Pemberantasan Korupsi, 2024)
One of the public participation forms in the democratic setting is the mechanism of lobbying. In various countries, this mechanism has been regulated by the governments in accordance with recommended standards. This paper seeks to examine the international standards and recommendations as well as the implementation of lobbying regulations in multiple countries. The analysis focuses on the efficacy of lobbying regulation in different contexts, including issues such as insufficient disclosure, noncompliance, and enforcement mechanisms, which vary between countries. Our finding is that the efficacy of lobbying regulation in the United States is facing persistent challenges, including insufficient disclosure and potential noncompliance, which require deeper scrutiny and enforcement mechanisms. In Ireland, inadequate mitigation exists in regulating international lobbying and extraterritorial enforcement, a notable deficiency that needs to be addressed and solved. In Australia, however, there has been a progression from minimalistic approaches to more stringent legislative frameworks, albeit predominantly focused on third-party lobbyists, and therefore, there is still a lack of monitoring of other types. This situation underscores the need for comprehensive reform to address waning public trust in democratic institutions. Finally, we propose a recommendation for the lobbying regulation to be applied in Indonesia in order to enhance integrity and promote transparency throughout the policy formulation process.